Resistorless current-mode universal filter using current differencing cascaded transconductance amplifiers - Duangmalai, Danupat; Jaikla, Winai (My University, 2018)
In this paper, a new realization of a current-mode universal filter using the current differencing cascaded transconductance amplifiers (CDCTAs) and grounded capacitors is proposed. The tune of the natural frequency and the quality factor can be independently done with electronic method by adjusting the bias current. The proposed filter provides low-pass, high-pass and band-pass responses in the same circuit. The input current node has low impedance and the output current nodes have high impedance which is attractive for cascading without the use of the current buffer. The performances of the proposed filter are verified by numerous PSpice simulations using the model parameters of the NR200N and PR2000N bipolar junction transistor arrays ALA400 from AT&T with ±2 V supply voltages.
Keywords: current differencing cascaded transconductance amplifier; current-mode circuit; electronic controllability; grounded capacitor; universal filter